From the Lens of Constructivism: The Culture & History of Johor in International Relations via the Johor Heritage Foundation - Jalaluddin, Fairuzahri; Azari, Muhammad Aiman Nasuha; Thukiman, Kassim (STIE Malangkucecwara, 2024)
Why are certain state actors actively promoting their cultural and historical heritage to others?. While many scholars in the field of international relations (IR) often stress the importance of national interest in understanding a state or country's behaviour, IR is a multifaceted field that cannot be fully comprehended from a single perspective. Therefore, this article explores the significance of culture and history within international relations by examining key concepts of Constructivism, an IR theory, with Johor, a prominent southern state of Malaysia, as a case study. The primary objective of this article is to explore the Constructivism perspective on the role of Johor's culture and history in its international relations. Additionally, the article comprehensively discusses the role of the Johor Heritage Foundation (JHF), a statutory body under the state government, in preserving the culture and history of this state. For findings, Johor through JHF is a significant state which highly emphasized on the importance of culture and history within its rapid development. The qualitative methodology and relevant themes were analysed and categorised to illustrate the different components of the role of Johor's culture and history within international relations from the perspective of Constructivism.